Peran Metode Role Playing dalam Meningkatkan Pembiasaan Perilaku Hidup Bersih dan Sehat Anak Usia Dini: The Role of the Role-Playing Method in Fostering Clean and Healthy Living Habits Among Early Childhood Children - Ade Rina; Mufassirul Alam (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Clean and healthy living behaviors (PHBS) are a crucial aspect that needs to be instilled from an early age to foster positive daily habits. However, the cultivation of these habits among young children remains suboptimal, as evidenced by their limited ability to maintain personal and environmental hygiene. This situation is influenced by teaching methods that lack engagement and fail to fully involve children in active participation fully. This study aims to enhance the adoption of clean and healthy living habits among children through the implementation of the Role-Playing method. The study employs Classroom Action Research (CAR) with a mixed-methods approach, combining qualitative analysis of the learning process with quantitative descriptive analysis of the children's progress in these habits. The research was conducted over two cycles, comprising the stages of planning, action implementation, observation, and reflection. The subjects were 15 children aged 5–6 years at the Nurul Muslimin Early Childhood Education (PAUD) center. Data were collected through observation, documentation, and field notes, then analyzed descriptively based on observation results and the percentage of children's progress in each cycle. The results indicate that the Role-Playing method successfully improved the adoption of clean and healthy living habits over time. In the pre-cycle stage, the majority of children (61.11%) fell into the "Not Yet Developed" category. Following the intervention in Cycle I, the "Very Well Developed" category rose to 16.67%, and subsequently increased significantly to 88.89% in Cycle II. Thus, the Role-Playing method is effective in fostering clean and healthy living habits through learning that is active, interactive, enjoyable, contextual, and based on direct experience.